Does Diet Have a Role in the Treatment of Alzheimer's Disease? - Thelen, Mitchell; Brown-Borg, Holly M. (Frontiers in Aging Neuroscience, 2020)
The aging process causes many changes to the brain and is a major risk factor for the development of neurodegenerative diseases such as Alzheimer’s Disease (AD). Despite an already vast amount of research on AD, a greater understanding of the disease’s pathology and therapeutic options are desperately needed. One important distinction that is also in need of further study is the ability to distinguish changes to the brain observed in early stages of AD versus changes that occur with normal aging. Current FDA-approved therapeutic options for AD patients have proven to be ineffective and indicate the need for alternative therapies. Aging interventions including alterations in diet (such as caloric restriction, fasting, or methionine restriction) have been shown to be effective in mediating increased health and lifespan in mice and other model organisms. Because aging is the greatest risk factor for the development of neurodegenerative diseases, certain dietary interventions should be explored as they have the potential to act as a future treatment option for AD patients.